2004
DOI: 10.1074/jbc.m311088200
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Selection Determines Agonist-specific Ca2+ Signals in Pancreatic Acinar and β Cells

Abstract: How different extracellular stimuli can evoke different spatiotemporal Ca2؉ signals is uncertain. We have elucidated a novel paradigm whereby different agonists use different Ca 2؉ -storing organelles ("organelle selection") to evoke unique responses. Some agonists select the endoplasmic reticulum (ER), and others select lysosome-related (acidic) organelles, evoking spatial Ca 2؉ responses that mirror the organellar distribution. In pancreatic acinar cells, acetylcholine and bombesin exclusively select the ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
192
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(217 citation statements)
references
References 44 publications
(63 reference statements)
17
192
5
Order By: Relevance
“…Perhaps most significantly, we provide the first direct evidence in support of the proposal (17,19) that NAADP may selectively elicit Ca 2ϩ signals from a lysosome-related Ca 2ϩ store alone, which may then be amplified by CICR from the SR/ER via RyRs. Furthermore, our data show that NAADP- Red-labeled organelle and ryanodine receptors labeled with BODIPY-ryanodine that co-localize in the same focal plane.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Perhaps most significantly, we provide the first direct evidence in support of the proposal (17,19) that NAADP may selectively elicit Ca 2ϩ signals from a lysosome-related Ca 2ϩ store alone, which may then be amplified by CICR from the SR/ER via RyRs. Furthermore, our data show that NAADP- Red-labeled organelle and ryanodine receptors labeled with BODIPY-ryanodine that co-localize in the same focal plane.…”
Section: Discussionmentioning
confidence: 62%
“…Previously, we have shown that NAADP induces Ca 2ϩ bursts from a thapsigargin-insensitive store other than the SR and that these local Ca 2ϩ signals are then amplified by subsequent CICR from the SR via RyRs (13). We therefore investigated the possibility that the NAADP-sensitive Ca 2ϩ store in vascular smooth muscle is an acidic, lysosome-related store as previously suggested by investigations on other cell types (17,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, in sea urchin eggs, the characterization of NAADP induced Ca 2ϩ release revealed that a receptor/channel different from the InsP 3 receptor or the ryanodine receptor (RyR) is involved (11,18). In addition, Lee's group obtained evidence for a non-ER Ca 2ϩ store sensitive to NAADP in stratified sea urchin eggs (19) that was finally identified as a lysosomal compartment (20)(21)(22)(23). Recent evidence indicates that the novel NAADP receptor on lysosomes is the Ca 2ϩ channel transient receptor potential, mucolipin 1 (TRP-ML1; 24,25).…”
mentioning
confidence: 99%